2005
DOI: 10.1021/la0518905
|View full text |Cite
|
Sign up to set email alerts
|

Sum Frequency Generation Studies of Surfaces of High-Surface-Area Powdered Materials

Abstract: We report the first observation of sum frequency generation (SFG) photons on high-surface-area powders, critically important materials in heterogeneous catalysis. We utilize SFG in total internal reflection (TIR) geometry and show that the TIR-SFG approach markedly reduces the destructive interference associated with nonlinear optical spectroscopy of small particle surfaces, making SFG studies of high-surface-area powders possible. The index of refraction of materials and their distance from the TIR-SFG prism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…Consequently, the SFG field may be different on opposite nanoparticle sides, breaking the inversion symmetry. 22 Assuming that inversion symmetry holds, the top nanoparticle surface will be the dominant contributor to the SFG signal and the pyridinium cation will be oriented in an upright conformation, as shown schematically in Figure 4.…”
Section: Surface Coverage σ (Molecules/cmmentioning
confidence: 99%
“…Consequently, the SFG field may be different on opposite nanoparticle sides, breaking the inversion symmetry. 22 Assuming that inversion symmetry holds, the top nanoparticle surface will be the dominant contributor to the SFG signal and the pyridinium cation will be oriented in an upright conformation, as shown schematically in Figure 4.…”
Section: Surface Coverage σ (Molecules/cmmentioning
confidence: 99%
“…Recent studies have demonstrated that SFG is a powerful and information-rich probe of nanostructured surfaces [193][194][195], and surface behaviors with nanoparticles [159,[196][197][198][199][200]. In the following sections, recent advancements that explore the utility of SFG as a powerful and unique technique to study surfaces/interfaces containing nanoparticles will be covered.…”
Section: Sfg Studies At the Nano-bio Interfacementioning
confidence: 99%
“…Later, Rupprechter used SFG to study the CO molecules adsorbed on Pd or Pt nanoparticles at controlled pressure and temperature [202,203]. Yeganeh et al [197] demonstrated that the total internal reflection (TIR) configuration reduces destructive interference associated with non-linear optical spectroscopy of small particles making SFG studies of small objects possible. In a similar way, SFG spectroscopy in total internal reflection geometry was successfully applied to study the adsorption and oxidation of CO on monolayer films of platinum cubic nanoparticles [198].…”
Section: Sfg Studies At the Nano-bio Interfacementioning
confidence: 99%
“…26,27 There are also recent reports of linking wet-chemically synthesized shape-controlled colloidal nanoparticles to (surface-modified) quartz prisms ( Figure 2d) and using total internal reflection geometry to yield higher signal. 28,29 The latter represents a promising route of applying VSFG to technical materials.…”
Section: Catalytically Active Surfacesmentioning
confidence: 99%